2022
DOI: 10.1080/14767058.2022.2083494
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and obstetric outcomes of listeria pregnancy: insights from a national cohort

Abstract: ICD-10-CM Diagnosis / Procedure Code or DRG (discharge date on or after 10/1/2015) Identification of Maternity-associated hospitalization Source: Healthcare cost and utilization project (https://www.hcupus.ahrq.gov/db/quality.pdf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…One study enrolled 134 pregnant women hospitalized for Listeria infection from 2007 to 2018 in the United States and found that the risk of severe maternal morbidity was 21.2-time higher in women with Listeria during pregnancy than in those without, specifically the risk of sepsis (28.1% vs 0.1%, P < 0.001), shock (1.4% vs 0.0%, P < 0.001) and acute respiratory distress syndrome (2.8% vs 0.1%, P < 0.001). 10 In addition, maternal infection could be transmitted vertically to the fetus, leading to fetal or neonatal infection with severe complications like fetal distress, preterm birth, miscarriage or stillbirth, neonatal sepsis, neonatal asphyxia and meningitis. 9 Therefore, it remains huge challenge for accurate diagnosis and timely treatment of Listeria monocytogenes infection.…”
Section: Introductionmentioning
confidence: 99%
“…One study enrolled 134 pregnant women hospitalized for Listeria infection from 2007 to 2018 in the United States and found that the risk of severe maternal morbidity was 21.2-time higher in women with Listeria during pregnancy than in those without, specifically the risk of sepsis (28.1% vs 0.1%, P < 0.001), shock (1.4% vs 0.0%, P < 0.001) and acute respiratory distress syndrome (2.8% vs 0.1%, P < 0.001). 10 In addition, maternal infection could be transmitted vertically to the fetus, leading to fetal or neonatal infection with severe complications like fetal distress, preterm birth, miscarriage or stillbirth, neonatal sepsis, neonatal asphyxia and meningitis. 9 Therefore, it remains huge challenge for accurate diagnosis and timely treatment of Listeria monocytogenes infection.…”
Section: Introductionmentioning
confidence: 99%
“…10 Severe adverse outcomes have also been observed outside outbreak settings. A retrospective US cohort 11 study of 134 pregnant women hospitalised with listeriosis during 2007-18 reported higher rates of severe maternal morbidity than in those without listeriosis (30•9% vs 1•6%, respectively; p<0•001; 21•2-fold higher adjusted risk; 95% CI 14•0-31•9) including acute respiratory distress syndrome (2•8% vs 0•1%, respectively; p<0•001), mechanical ventilation (1•4% vs 0•0%, respectively; p<0•001), sepsis (28•1% vs 0•1%, respectively; p<0•001), and shock (1•4% vs 0•0%, respectively; p<0•001). Pregnant women with listeria also had higher rates of caesarean delivery, as compared with those who did not (57•9% vs 32•9%, respectively; p<0•001), preterm birth (61•3% vs 7•7%, respectively; p<0•001), and stillbirth (13•5% vs 0•7%, respectively; p<0•001).…”
mentioning
confidence: 99%
“…Pregnant women with listeria also had higher rates of caesarean delivery, as compared with those who did not (57•9% vs 32•9%, respectively; p<0•001), preterm birth (61•3% vs 7•7%, respectively; p<0•001), and stillbirth (13•5% vs 0•7%, respectively; p<0•001). 11 The US Food and Drug Administration warns that symptoms can develop within a few hours or as late as 2-3 days after eating contaminated food, although intervals of up to 3 months have been reported. Realtime PCR from bacterial isolates should be used for rapid and accurate diagnosis.…”
mentioning
confidence: 99%